Fatal nephrobronchial fistula arising from xanthogranulomatous pyelonephritis: a case report - Burbano, María Alejandra; Nati-Castillo, H. A.; Castaño-Giraldo, Natalia; López, Gildardo; Placencia-André, Romina; Salazar-Santoliva, Camila; Villavicencio-Gomezjurado, Melissa; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2024)
Introduction Nephrobronchial fistula is an exceptionally rare complication of renal infections, including the uncommon xanthogranulomatous pyelonephritis. Existing literature is limited to a few case reports, with antibiotic therapy and nephrectomy being the preferred treatments. Case We present the case of a 63-year-old woman with a history of recurrent xanthogranulomatous pyelonephritis in her right kidney, requiring drainage through lumbotomy. She presented with a chronic dry cough and weight loss, without other noticeable symptoms. Imaging suggested a pulmonary abscess and nephrobronchial fistula. Despite antibiotic treatment and surgical intervention, her condition progressed fatally. Conclusion Nephrobronchial fistulas are extremely complications of renal infections, often presenting with nonspecific symptoms. This case highlights their significant impact on morbidity and mortality, especially in resource-limited settings, and underscoring the urgent need for prompt diagnosis and treatment.